Penggunaan Media Pembelajaran Berbasis Wordwall di Era Merdeka Belajar untuk Meningkatkan Minat Belajar Siswa SD - Rany Andriany; Warsiman Warsiman (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
One of the most important things in learning is the use of appropriate media. The right media can affect student learning success. However, it has so far been neglected by many teachers/professionals. The research objective is to increase students' interest in learning through Wordwall-based media. This study uses Classroom Action Research (CAR). The data source for this research were 26 grade V students at SDN Turi II Tambakrejo. The results of the study show that learning with Wordwall-based media can increase students' interest in learning. This increase can be seen in student learning outcomes in the preliminary study an average of 56,3. Meanwhile, in Cycle I, it was 72,3 and the average in Cycle II was 83,15. In addition, there are also observations on the proportion of nine indicators of student interest in learning. Students who are developing quite well (BCB) and students who are developing very well (BSB) experience an increase in the percentage of preliminary studies of only 59% when given Classroom Action Research, an increase of 77% in cycle I, while in cycle II it reaches 90%. The conclusion is that using Wordwall-based media can increase student learning interest. Therefore, it is hoped that teachers/educators will try to implement a Wordwall-based learning environment to increase students' interest in learning at school.